2020
DOI: 10.1007/s00402-020-03338-1
|View full text |Cite|
|
Sign up to set email alerts
|

Is debridement beneficial for focal cartilage defects of the knee: data from the German Cartilage Registry (KnorpelRegister DGOU)

Abstract: Introduction Focal cartilage defects of the knee are often treated with arthroscopic debridement. Existing literature discussing the benefit of debridement for small articular cartilage lesions is scarce, especially if the debridement was not part of a combined operative cartilage procedure including meniscal and ligament repair. The purpose of this study was to examine the patients´ benefit after arthroscopic debridement for the treatment of isolated focal chondral defects with or without partial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…long term follows up of this treatment found improved clinical results and less serious degenerative changes [22]. Studies have shown that focal chondropathies treated with debridement having excellent functional results, no matter how large or deep the defect may be [23].…”
Section: Arthroscopic Debridementmentioning
confidence: 94%
“…long term follows up of this treatment found improved clinical results and less serious degenerative changes [22]. Studies have shown that focal chondropathies treated with debridement having excellent functional results, no matter how large or deep the defect may be [23].…”
Section: Arthroscopic Debridementmentioning
confidence: 94%
“…Weißenberger et al 3 from German Cartilage Registry data analysis including 126 patients with focal cartilage injuries at 1year follow-up, found significant KOOS score improvement in lesions less than 2 cm 2 in size with or without concomitant partial meniscectomy. However, patients with lesions less than 2 cm 2 in size with concomitant partial meniscectomy showed no significant benefit.…”
Section: The Evidence On Arthroscopic Debridementmentioning
confidence: 99%
“…Arthroscopic debridement (AD) is one of the most common procedures in treating cartilage lesions. [1][2][3] AD encompasses the smoothening of fibrillation, flaps, or loose bodies of the cartilage surface and creating right-shouldered and stable margins using arthroscopic instruments like shavers or curettes. 4 However, despite its comprehensive implementation in the surgical treatment of osteochondral lesions of the talar dome (OLT) during the last century, its practice is rather abandoned nowadays.…”
Section: Introductionmentioning
confidence: 99%
“…Chondroplasty as a primary procedure for focal articular cartilage defects has demonstrated inconsistent results in the literature. 9 , 18 , 19 , 20 , 21 Specifically, chondroplasty was not shown to provide symptomatic benefit as compared with observation alone in a randomized controlled trial, 19 or provide significant benefit in delaying arthroplasty. 18 However, other series have suggested that chondroplasty for articular cartilage defects less than 2 cm 2 and in the absence of concurrent meniscal pathology may be efficacious.…”
mentioning
confidence: 99%
“… 18 However, other series have suggested that chondroplasty for articular cartilage defects less than 2 cm 2 and in the absence of concurrent meniscal pathology may be efficacious. 9 , 21 Given the potential for meaningful clinical benefit and further informed decision-making following direct defect visualization, probing, and chondroplasty at the time of initial diagnostic arthroscopy, a single-stage definitive cartilage restoration procedure (OCA, minced cartilage allograft, etc.) may be found to be unnecessarily aggressive for certain patients.…”
mentioning
confidence: 99%